2019
DOI: 10.1080/17518423.2019.1655677
|View full text |Cite
|
Sign up to set email alerts
|

Upper-extremity Spasticity-reducing Treatment in Adjunct to Movement Training and Orthoses in Children with Cerebral Palsy at Gross Motor Function- and Manual Ability Classification System Levels IV-V: A Descriptive Study

Abstract: Covering a 20-year period of work with children with severe cerebral palsy (CP) within a Swedish habilitation service, changes in passive wrist extension with fingers extended (PWE-FE) and current hand function are described and compared between children receiving systematic upper-extremity treatment with botulinum neurotoxin type A and intervention programs from before 7 years of age (Group 1, n = 7), those whom for various reasons did not undergo this treatment (Group 2, n = 10), and those not having the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…4 Systematic outpatient treatment with BTX injections, combined with physiotherapy, occupational therapy, plaster, and/ or orthoses associated with rehabilitation team treatment, has been recommended in several studies to achieve the set objectives successfully. 3,4,45,59,82,60 Hareb et al conducted a non-systematic review. They reported that the administration of BTX is well-supported in the literature, especially for spasticity in children over 2 years old, requiring a multidisciplinary approach.…”
Section: Methodsmentioning
confidence: 99%
“…4 Systematic outpatient treatment with BTX injections, combined with physiotherapy, occupational therapy, plaster, and/ or orthoses associated with rehabilitation team treatment, has been recommended in several studies to achieve the set objectives successfully. 3,4,45,59,82,60 Hareb et al conducted a non-systematic review. They reported that the administration of BTX is well-supported in the literature, especially for spasticity in children over 2 years old, requiring a multidisciplinary approach.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the ingredients under fitness encompass ideas such as managing pain, contractures, and deformity, increasing physical activity, and ensuring adequate nutrition, sleep, and gastrointestinal function. Among the intervention ingredients related to prevention, we highlight hip surveillance 56 and postural management [57][58][59][60][61][62][63][64][65][66][67][68] as components that may minimize the risk or severity of musculoskeletal impairments. Given the reduced motor repertoire of this population, increased physical activity may be promoted by adapting activities to the child's level of ability so that child-initiated movement is possible.…”
Section: Fitnessmentioning
confidence: 99%
“…En general, los ingredientes relacionados con el estado físico engloban ideas como el manejo del dolor, contracturas y deformidad, aumento de la actividad física y consecución de una nutrición, sueño y función gastrointestinal adecuados. Entre los ingredientes de intervención relacionados con la prevención, destacamos la vigilancia de la cadera 56 y el manejo postural [57][58][59][60][61][62][63][64][65][66][67][68] como componentes que pueden minimizar el riesgo o la severidad de las alteraciones musculoesqueléticas. Debido al reducido repertorio motor de esta población, se puede promover el aumento de la actividad física adaptando las actividades al nivel de capacidad del niño, de modo que sea posible el movimiento autoniciado.…”
Section: Estado Físicounclassified